Strengthening Rural Livelihoods Through Community Learning Centers in Northern Bangladesh - Humaira, Bushra; Miajy, Abdullah; Haque, Abdul; Ahmed, Sharif; Bhandari, Humnath (International Rice Research Institute, 2025)
In the small village of Ishwarpur in northern Bangladesh, 30-year-old Hafiza Begum once spent her days caring for her children, managing household responsibilities, and assisting her husband on their small farm. Like many rural women, she had limited access to modern agricultural knowledge and technologies. Her life changed when she attended a vermicompost training at her local Community Learning Center (CLC), established by the International Rice Research Institute (IRRI) under the CGIAR Initiative on Mixed Farming Systems (MFS)